IMPLEMENTASI KEBIJAKAN PERDA NOMOR 4 TAHUN 2010 TENTANG BANTUAN KEUANGAN KEPADA PARTAI POLITIK DI KOTA SINGKAWANG - Hikman Al Wizar E.01109106 (FISIP Universitas Tanjungpura, 2013)
This thesis raised the issue during the process of granting financial assistance to political parties in The unity of the nation, political and Societal Protection Singkawang. Writing a thesis is intended to provide an understanding of the implementation of the granting of financial assistance to the political party that has been done by the Government to assist Singkawang political education and operational activities of the Secretariat of the political parties in Singkawang. This research included in the kind of research descriptive with a qualitative paradigm. Problems of national unity, political and community protection singkawang city is still lack of consciousness political party in giving report all of its answers the use of financial assistance in on time. Suggestions for research is expected also to the Government of Singkawang to revisit the rules of Singkawang Region number 4 of 2010 about financial assistance to political parties, especially on the part that regulates sanctions for political parties that are late providing reports to Liability for the deterrent effect of political parties which have provided Liability Reports.Keywords: political party, financial support, accountability report.